PENGARUH POLA LATIHAN SIRKUIT TRAINING DAN LARI FARTLEK TERHADAP DAYA TAHAN AEROBIK ATLET PENCAK SILAT PAGAR NUSA - Setyawan, Trinovandhi; Adi Pawitra, Paulus Rah Adi; Yahya, Alfian; Budiono, Dwi (STKIP Melawi, 2024)
Abstract: The purpose of this study was to determine the effect of circuit training and fartlek running on increasing the aerobic endurance of Pagar Nusa Pencak Silat athletes in Batu City. The results of the study are as follows, the results of the pre-test of the training circuit have the highest score of 40.5 and the lowest score of 21.8 with an average of 33.34 with a standard deviation of 6.67. While the fartlek run has the highest score of 34.3 and the lowest score of 27.9, the average data is 30.70 with a standard deviation of 2.36. The results of the post-test of the training circuit have the highest score of 44.5 and the lowest score of 28.3 with an average of 37.31 with a standard deviation of 5.83. Meanwhile, the fartlek run has the highest score of 37.8 and the lowest score of 30.2, with an average data of 34.35 with a standard deviation of 2.41. So that it can be seen that there is no significant difference in the effect between circuit training and flex running. Researchers provide suggestions. This research still needs to be further developed in the hope of providing more significant data as a comparison between circuit training treatment and fartlek running by adding more research subjects. With the addition of research subjects, it is expected to get more different data and get more significant differences in the resultsKeywords: Circuit Training, Fartlek Running, Aerobic Endurance Abstrak: Tujuan penelitian ini adalah untuk mengetahui pengaruh latihan sirkuit dan lari fartrek terhadap peningkatan daya tahan aerobik atlet Pencak Silat Pagar Nusa Kota Batu. Berikut temuannya: Nilai tertinggi sebesar 40,5, nilai terendah sebesar 21,8, dan mean standar deviasi sebesar 6,67. Sedangkan nilai tertinggi Fartlek Lari sebesar 34,3, nilai terendah sebesar 27,9, rata-rata data sebesar 30,70, dan standar deviasi sebesar 2,36. Setelah dilakukan pengujian rangkaian latihan diperoleh nilai tertinggi sebesar 44,5, nilai terendah sebesar 28,3, nilai mean sebesar 37,31, dan standar deviasi sebesar 5,83. Sedangkan nilai tertinggi Fartlek Lari sebesar 37,8, nilai terendah sebesar 30,2, rata-rata data sebesar 34,35, dan standar deviasi sebesar 2,41. Dengan kata lain, tampaknya tidak ada banyak perbedaan dalam efek latihan sirkuit dan lari cepat. Peneliti memberikan saran. Penelitian ini perlu dikembangkan lebih lanjut dengan memasukkan lebih banyak topik penelitian dengan harapan dapat memberikan data yang lebih bermakna sebagai perbandingan antara latihan sirkuit dan lari fartlek. Dengan menambahkan tema penelitian, kita berharap memperoleh data yang lebih beragam dan hasil yang berdampak pada varians yang lebih besar.Kata Kunci: Sirkuit Training, Lari Fartlek, Daya Tahan Aerobik